The assessment of the argyrophylic nucleolar organizer regions (AgNORs) count in serous ovarian neoplasms - Bieńkiewicz, Andrzej; Suzin, Jacek; Gottwald, Leszek; Danilewicz, Marian (Menopause Review/Przegląd Menopauzalny, 2003)
Aim of study: To evaluate the usefullnes of argyrophylic nucleolar organizer regions (AgNORs) analysis in the assessment of malignancy in the serous ovarian neoplasms. Material and methods: 110 women who underwent a surgical procedure between 1998–2002 in our department due to serous ovarian neoplasms (29 adenomas, 12 borderline and 69 carcinomas) were covered by the study. The specimens were prepared according to the method described by Howell and Ploton. The mean number of AgNORs per nucleus (mAgNOR) and the mean percentage of nuclei with five or more AgNORs per nucleus (pAgNOR) were counted in the light microscope in 100 randomly chosen epithelial cell nuclei at 400 x oil immersion magnification. Results: The mAgNOR and pAgNOR mean numbers were respectively: 1.925±0.361 and 0.897±0.860 in adenomas, 2.908±0.258 and 4.167±2.401 in borderline tumors, 4.310±0.811 and 39.739±20.580 in cancers. According to the grading of cancers it was as follows 3.742±0.253 and 22.118±10.030 in G1 tumors, 4.127±0.556 and 35.524±13.938 in G2 tumors, and 4.745±0.922 and 52.258±20.651 in G3 neoplasms. All the differences were statistically signifficant. The correlation between the tumor type and mAgNOR as well as pAgNOR from adenomas to G3 cancers was found. Conclusions: We found an increase in mAgNOR and pAgNOR from serous adenomas through borderline tumors to cancers. Together with the tumor grade increase, an increase in mAgNOR and pAgNOR was observed. These findings together with easy methods and low costs make the evaluation of AgNORs at potential helpful method in the assessment of serous ovarian neoplasms.